COMPLEX ENTERITIS WITH FLEA INFESTATION IN DOMESTIC CAT - Ni Putu Dewi Setia Sari; Putu Devi Jayanti; Sri Kayati Widyastuti (Buletin Veteriner Udayana, 2024)
Complex enteritis in this case was caused by infestation of Dipylidium caninum, Isospora sp. and Ctenocephalides felis fleas infestation which are vectors of Dipylidium caninum. The writing of this article is to identify the results of anamnesis, clinical symptoms, and examination results in cat cases, to determine the diagnosis and evaluate therapy. The case is a female cat named Chloe, five months old, tortie in color with body weight 1.65 kg. The owner tell the cat had been diarrhea with blood and worms in feces since last week and the cat sometimes scratched body. Praesens status shows Capillary Refill Time (CRT) is more than 2 seconds and increase in respiratory frequency. Trichogram showed hair breaks and flea comb test showed infestation of flea. After identified under microscope, the cat was infested with Ctenocephalides felis. The results of stool examination showed Dipylidium caninum proglottids and Isospora sp oocysts. The blood test results showed hypochromic normocytic anemia. The cat diagnosed with complex enteritis with flea infestation. Therapy given by injection of ivermectin 0.032 ml, SC, twice with interval of 14 days; antihistamine injection diphenhydramine HCl 0.08 ml, SC; anthelmintic pyrantel embonate and praziquantel 1 tablet/4kg BW, PO interval 14 days; sulfamethoxazole-trimethoprim 30 mg/kg BW, PO, q12h, for 7 days; kaolin pectin 1.5 ml/kg BW, PO, q12h, for 10 days. Supportive therapy is providing vitamin B complex 1 tablet, PO for 7 days and changing feed to support digestive condition. Evaluation on the 10th day showed an improvement to good in the condition of faeces change FCS and normal defecation frequency. Stool examination was carried again, macroscopically no blood or proglottids were found and microscopic examination found no worm eggs or oocysts. Regular deworming and vaccinated of cat are important.